2016
DOI: 10.1002/jip.1451
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Personality of the Public Safety Offender and Non‐offender using Decision Trees: The Case of Colombia

Abstract: The aim of this paper was to create a decision tree (DT) to identify personality profiles of offenders against public safety. A technique meeting this requirement was proposed that uses the C4.5 algorithm to derive decision rules for personality profiling of public safety offenders. The Mini-Mult test was used to measure the personality profiles of 238 individuals. With the test results as our database, a C4.5 DT was applied to construct rules that classify each profile into one of two groups, those without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Then, the tree was pruned, using a tenfold cross validation procedure to determine the optimal tree size. In this way, the tree whose complexity parameter minimized the mean error of the cross-validation ( x error ) was selected [16,50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the tree was pruned, using a tenfold cross validation procedure to determine the optimal tree size. In this way, the tree whose complexity parameter minimized the mean error of the cross-validation ( x error ) was selected [16,50].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, although traditional statistical methods focusing on mere descriptions of the phenomena continue to be used in investigations, the use of more sophisticated statistical analysis methods such as multivariate techniques has become more popular. One of the advantages of these statistical procedures is that they consider the combined relationships between all elements that are linked to homicides, thereby ensuring a better understanding of the phenomena and permitting useful conclusions to be reached [6,15,16,17]. In this way, studies focusing on prediction stand out, specifically those focusing on the applied nature of criminal profiling during police investigations, which has been conceived as a supplementary technique to help in the identification and arrest of criminals [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that knowledge acquisition is the most common processes used to enhance AI systems (N = 6), followed by both knowledge creation and knowledge application/decision-making process (N = 6), knowledge sharing (N = 2), and Knowledge discovery with the least number of studies (N = 1). Referring to Table 4, it seems that knowledge application and decision-making processes have a positive impact on Neural Networks, including ANN, RNN, and CNN [31], Decision Trees [33], and Chatbots [56]. On the other hand, [52] argued that knowledge management application and decision making could have some negative impact on Neural Networks, including ANN, RNN, and CNN, in some applications.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial neural networks and data mining work in parallel for the CRM system in order to generate knowledge about customers' behaviors and to predict their willingness to purchase specific items [32]. Additionally, in [33] study, they express the importance of using knowledge management in order to feed the AI system as it is essential for personal characterization, which used to improve public safety using the decision tree algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Valuable though these three analyses are, they all confine their methodologies to the use of Logistic Regression as a data classifier. Studies in other contexts comparing different classifiers have shown that that their performance can vary significantly depending on the data domain they are applied to [ 29 35 ]. This suggests that classification techniques other than Logistic Regression should be evaluated to determine how well they perform comparatively with criminal network data.…”
Section: Introductionmentioning
confidence: 99%